2008
DOI: 10.1007/s10570-008-9246-0
|View full text |Cite
|
Sign up to set email alerts
|

Endoxylanase action towards the improvement of recycled fibre properties

Abstract: The nature of recycled paper fibres varies widely. Those fibres contain high amounts of heteroxylans and lignin besides cellulose. In order to study the potential effect of xylanases on the quality of recycled fibres, chemithermomechanical pulp fibres (CMTP) are used as model substrates owing to their high content in non-cellulosic components. It has been found that the morphology of CTMP fibres changes by means of xylanase treatment. Treatments of CTMP fibres with an endoxylanase result in an improved sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The dispersed unbleached Eucalyptus Kraft Pulp was used to make handsheets employing a standard handsheet making apparatus (G 8E, Gockel & Co. GmbH, München). The basis weight of the handsheets was 60 g/m 2 , and the wet substrates were dried for 10 min at a temperature of 95 ℃ by laying a sheet on a heated plate of the dryer of the aforementioned standard handsheet making apparatus. This sheet was labeled as virgin paper (cycle 0).…”
Section: Preparation Of Recycled Handsheetsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dispersed unbleached Eucalyptus Kraft Pulp was used to make handsheets employing a standard handsheet making apparatus (G 8E, Gockel & Co. GmbH, München). The basis weight of the handsheets was 60 g/m 2 , and the wet substrates were dried for 10 min at a temperature of 95 ℃ by laying a sheet on a heated plate of the dryer of the aforementioned standard handsheet making apparatus. This sheet was labeled as virgin paper (cycle 0).…”
Section: Preparation Of Recycled Handsheetsmentioning
confidence: 99%
“…Post-consumers' paper and paperboard are gathered as waste paper, which have become the main source of papermaking raw materials [2] and, thus, not only mitigate the problem of scarce wood resources but also reduce the issues that are associated with waste generation and final disposal. Unfortunately, using waste paper as recycled material for papermaking results in the loss of strength and the reduction of wet flexibility and bonding properties of the fibers, which are caused by hornification [3] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the unchanged fiber morphology of the fibers pretreated with CBDs, especially fiber length, plays a critical role in the development of the tensile index of the handsheet. López-Lorenzo et al (2003) reported that the relative bonding area, flexibility, and fibrillation of fibers can be modified by CBDs and by cellulases with CBDs to improve the properties of both fiber and paper. The handsheet tensile and tear indices of the pulps pretreated with CBDs that were obtained in the present study confirm that CBDs can modify the fiber surface by increasing the flexibility and swelling ability (WRV) of the fiber or by splitting the cellulose chain and releasing more active surfaces for bonding, but they also reveal that CBDs may lower the strength of a single fiber and result in some reduction in the tear index.…”
Section: Effects Of Pretreatments With Cellulase and Cbds On The Phys...mentioning
confidence: 99%